Efficacy of wrist strategy coaching on handstand performances in novices: inverting explicit and implicit learning of skill-related motor tasks - Rohleder, J.; Vogt, T. (Science of Gymnastics Journal, 2019)
In gymnastics, mainstream handstand coaching emphasizes developing an aligned rigid body configuration, frequently leaving wrist-controlled balance work to implicit learning. However, skill-related motor behavioral research suggests the wrists to primarily contribute postural control in handstands. Considering recent research on handstands revealing experience-dependent motor behavior, the present study aimed to examine motor learning effects of explicit wrist usage coaching on handstand performances in skilled and less skilled novices. Therefore, twenty-five volunteering sport students served as participants completing a three-week training intervention which solely and explicitly addressed successful wrist usage during handstand. A video-tutorial introducing participants to the wrist strategy of hand balance preceded five practical training sessions that all neglected providing explicit postural advice. Participants performed three handstands on a plane gymnastics mat prior to (pre-test) and after (post-test) completing the training intervention. Standardized video recordings of each trial allowed retrospective group assignment (skilled and less skilled novices) based on pre-test mean balance times. With this, balance times, expert assessments (postural execution and balance control strategies) and goniometric analyses of shoulder and hip joint angles served to detect practical changes in handstand performances. Enhanced balance times as well as increased scores for postural execution and balance control strategies were revealed for less skilled novices (p < .05), but not for skilled novices (p > .05). Furthermore, in both groups changes in shoulder and hip joint angles failed significance. In conclusion, present findings suggest practitioners to make entirely unexperienced handstand learners explicitly aware of the wrist strategy`s operating principle.